Early detection of immune checkpoint inhibitor-related subclinical cardiotoxicity: A pilot study by using speckle tracking imaging and three-dimensional echocardiography - Xu, Aiqing; Yuan, Ming; Zhan, Xiaoping; Zhao, Gangjian; Mu, Guanyu; Wang, Tingting; Hu, Hailong; Fu, Huaying (Frontiers in Cardiovascular Medicine, 2022)
Background: Early detection of subclinical cardiotoxicity of immune checkpoint inhibitors (ICIs) therapy can be challenging. Objective: To evaluate subclinical cardiac dysfunction using the two-dimensional speckle tracking imaging (2D-STI) and three-dimensional echocardiography in Chinese patients. Methods: Fifty-five consecutive patients with malignant tumor treated by immunotherapy were included. They were examined by echocardiography before immunotherapy and after immunotherapy. Left ventricular ejection fraction (LVEF) calculated in three-dimensional imaging. Moreover, left ventricular global longitudinal peak systolic strain (LVGLS), left ventricular global circumferential peak systolic strain (LVGCS), right ventricular global longitudinal systolic strain (RVGLS), right ventricular free wall longitudinal peak systolic strain (RVFWLS) and tricuspid annular plane systolic excursion (TAPSE) were evaluated. Clinical and laboratory parameters were recorded. Cardiac toxicity events were defined as the presence of heart failure symptoms, LVEF reduction and increase in troponin. Subclinical cardiac toxicity was defined as cardiac dysfunction associated with ICIs treatment, with absent or delayed ICI-associated cardiotoxicity clinical symptoms. Results: Compared to baseline, the LVGLS, TAPSE and RVGLS significantly deteriorated after ICIs treatment ((-18.63±2.53) % vs. (-17.35±2.58) %, P=0.000; 18.29±6.23 vs. 14.57±3.81, P=0.0001; and (-18.45±4.65) % vs. (-14.98±3.85) %, P=0.0001 respectively). LVGLS (-17.35±2.58, P=0.000), TAPSE (14.57±3.81, P=0.0001), and RVGLS ((-14.98±3.85) %, P=0.0001) were decreased after ICIs immunotherapy. Kaplan-Meier curve analysis showed LVGLS was more sensitive than the cardiac toxicity events to assess ICIs-related subclinical cardiac dysfunction (Log Rank P=0.205). ROC curve showed the cut-off value of ΔLVGLS was -13%. Conclusions: Subclinical cardiac dysfunction can be detected using the two-dimensional speckle tracking imaging. LVGLS, RVGLS and TAPSE are more sensitive indices for detection.